2012
DOI: 10.1136/annrheumdis-2011-201191
|View full text |Cite
|
Sign up to set email alerts
|

‘Insights in the relationship of joint space narrowing versus erosive joint damage and physical functioning of patients with RA’

Abstract: Joint damage in the wrist, erosions more than JSN, is associated with impaired physical functioning even in patients with early RA with limited overall damage after 5 years tightly controlled treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 19 publications
1
16
0
1
Order By: Relevance
“…Structural joint damage can be visualized and quantified by using radiography and the Sharp scoring system or its modified versions, where the assessment of joint space narrowing (JSN), as a marker for the extent of cartilage damage, and the presence of bone erosion sites (ERO score) can be scored separately (van der Heijde, 1999). So far, studies in RA individuals that correlate functional impairment with JSN or ERO scores have demonstrated that cartilage damage could be more strongly associated than bone erosion with irreversible physical disability (Aletaha et al, 2011; Koevoets et al, 2013; Lillegraven et al, 2012; Navarro-Compan et al, 2015; Smolen et al, 2013; van der Heijde, 2011). However, those studies are limited by the fact that not all joints are affected by JSN and ERO, and that differential diagnosis of bone and cartilage erosion is sometimes difficult and might overlap.…”
Section: Introductionmentioning
confidence: 99%
“…Structural joint damage can be visualized and quantified by using radiography and the Sharp scoring system or its modified versions, where the assessment of joint space narrowing (JSN), as a marker for the extent of cartilage damage, and the presence of bone erosion sites (ERO score) can be scored separately (van der Heijde, 1999). So far, studies in RA individuals that correlate functional impairment with JSN or ERO scores have demonstrated that cartilage damage could be more strongly associated than bone erosion with irreversible physical disability (Aletaha et al, 2011; Koevoets et al, 2013; Lillegraven et al, 2012; Navarro-Compan et al, 2015; Smolen et al, 2013; van der Heijde, 2011). However, those studies are limited by the fact that not all joints are affected by JSN and ERO, and that differential diagnosis of bone and cartilage erosion is sometimes difficult and might overlap.…”
Section: Introductionmentioning
confidence: 99%
“…However, if one looks to the rheumatology experience for guidance, it should be kept in mind that treatment concepts designed for joint inflammation probably have to be adapted to suit the gastrointestinal tract. Intestinal damage may not necessarily cause a functional disability in the way a destroyed joint will . In our study, several of the patients with CD who had significant fibrotic tissue transformation (strictures) also had relatively mild symptoms during the following years and did not require intra‐abdominal surgery .…”
Section: Prognosismentioning
confidence: 62%
“…However, a SHS ≥ 1 (and thus more radiographic erosions) is associated with improved worker productivity. It is known that having erosions is associated with impaired physical functioning (32), and therefore one might expect lower worker productivity. But as these patients had a short disease duration before inclusion, resulting in minimal radiological damage to the joints at baseline and even during follow-up, the chosen cut-off point used for these analyses may have resulted in poor discrimination of the patients with and without damage, as most patients had no damage.…”
Section: Discussionmentioning
confidence: 99%